Anti-HPV16 oncoproteins siRNA therapy for cervical cancer using a novel transdermal peptide PKU12 - Deng, Yan; Song, Yi; Du, Quan; Wang, Chi Chiu; Li, Hu; Sui, Yi; Zhang, Yuying; Tang, Tao (Frontiers in Oncology, 2023)
In this study, an innovative transdermal peptide #PKU12 was developed based on Transdermal Peptide TD-1 and the anti-tumor effect of PKU12-based siRNA against HPV was investigated in vivo. Furthermore, transcriptome differences between PKU12 + siRNA treatment and control groups were compared to assess treatment effects. The top 5 up-regulated and down-regulated genes identified by RNA sequencing were further subjected to the survival analysis. The present study for the first time showed that this novel peptide could enhance the transdermal delivery of the siRNA targeting HPV16 L1, E6 and E7. PKU12-based siRNA delivery significantly repressed the mRNA expression levels of HPV16 L1, E6 and E7 in the SiHa xenograft tumors; and attenuated tumor growth as well. The RNA-sequencing results showed that a total of 586 DEGs were detected in the PKU12 + siRNA-treated tumor tissues compared to the control tumor tissues. The GSEA analysis revealed that DEGs were inversely associated with HIF-1 signaling pathway, TNF signaling pathway, AGE-RAGE signaling pathway, NF-kappa B signaling pathway, ferroptosis, IL-17 signaling pathway, ovarian steroidogenesis and rheumatoid arthritis. Further functional enrichment analysis revealed that the DEGs were significantly enriched in several key pathways including cytokine-cytokine receptor interaction, TNF signaling pathway, IL-17 signaling pathway.High expression of MYH1, MYH4, FGG, DEPP1 and ZBTB16was associated with shorter overall survival of patients with cervical cancer; high expression of SULT1E1, RAB3C, CXCR3 and PROX2 was associated with longer overall survival of patients with cervical cancer. In conclusion, the transdermal peptide PKU12 is potentially a good candidate of siRNA delivery vehicle for the treatment of cervical cancer.